Teacher Roles in the Digital Age of Schools under the Office of the Private Education Commission Dusit District, Bangkok - Charoensiri, Ladawan; Donprasit, Tuanjai (The Journal of Development Administration Research, 2022)
The objective of research is for 1) studying the character of digital aged teachers, especially teachers in school under the office of Private Education in Dusit district, Bangkok. 2) offering guidelines to promote the character of digital aged teachers in school under the office of Private Education in Dusit district, Bangkok, including managers and teachers in school under the office of Private Education in Dusit district for 295 people. The tools for data collection are questionnaire, scale assessment of the 5 levels, finding statistics by the mean and standard deviation. The research were found that: 1) character of digital aged teachers in school under the office of Private Education in Dusit district, Bangkok has high degree in all degree contain (1) The unedifying (2) Technology (3) The use of language/communication (4) The designers of learning (5) Good at questions (6) The quality control. (7) Coaches or directs. (8) Teamwork (9) The environment for learning (10) Creative thinking for problem solving. 2) guidelines to promote the character of digital aged teachers in school under the office of Private Education in Dusit district, Bangkok, we found that character of digital aged teachers is high. The managers could promote character of teachers to leaning technology for feasibility analysis and use to maximize performance, suitable for school, integrate and create innovation.